THEORETICAL PECULISRITIES OF TEACHING THE COURSE «BUSINESS UKRAINIAN LANGUAGE» IN A TECHNICAL INSTITUTION OF HIGHER EDUCATION - Ostapchuk, Svitlana; Kyrychenko, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
In the article describes the peculiarities of the educational and methodological course «Business Ukrainian language» for foreign students of technical profile, which was formed taking into account the need for them to acquire a high level of knowledge and skills of the culture of official business communication, which is an integral part of the training of a modern specialist with a higher education. The purpose of the research is to highlight the theoretical features of teaching the course "Business Ukrainian language" in the system of technical education institutions, to generalize and systematize the main concepts from the course of study, to determine the learning outcomes, which include mastering the rules of oral and written Ukrainian technical speech communication, the basics of professional terminology, types , the practical purpose and qualification of business papers and official documents, as well as the justification of the linguistic specificity of the professional sphere of communication through the ability to use various linguistic means of business communication. The results. Acquired knowledge and familiarization with the innovations of the new Ukrainian spelling, improvement of communicative and language competence of the oral form of business speech, deepening of theoretical knowledge and practical skills of compiling various texts of official content in compliance with established accentological, orthographic, orthoepic, terminological, lexical-phraseological, grammatical, punctuation and stylistic norms of the modern Ukrainian literary language, give future specialists the opportunity to build a career as a civil servant or highly technical specialist-manager and take a worthy place in society. Conclusions. The training course on "Business Ukrainian language" is a mandatory element in the training of specialists of higher education institutions of a technical profile, where knowledge of official business communication will be useful to future civil aviation engineers in industrial production, in scientific design and research units, to participate in the work of media resources, as well as administrative and management structures, both in private business and in state institutions of Ukraine